Employee Turnover and Operational Performance of Commercial Banks in Rwanda - Kayumba, Ephrem; Rusibana, Claude (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2021)
Employee turnover was the movement through which an organization hired and missed its employees. This might be voluntary, involuntary, internal transfer, and retirement turnover. The objective of this study was to analyse the employee turnover and operational performance of commercial banks in Rwanda, a case of KCB Bank Rwanda located in Nyarugenge District, Rwanda. The specific objectives were to analyse the effect of employee compensation on operational performance, to determine the impact of employee overscheduling on operational performance, and to find out the impact of employee favouritism on the operational performance of KCB Bank Rwanda. This quantitative research used the descriptive research survey design with questionnaire as research instrument where 80 questionnaires were distributed to 80 employees by using both physical and digital approaches forms due to situations of COVID-19. The data collection took six months and consisted of 15 Microsoft forms, 40 physical forms, and 25 emails responses. The data analysis was done by using Statistical Package for Social Science (SPSS) version 20 through which the census method was applied, and the descriptive method was used to make the conclusion and has been applied to determine the reliability and validity at 0.8%. This research contributed to the management of employee turnover to improve operational performance of commercial banks in Rwanda. It indicated that KCB Bank Rwanda recognized a considerable rate of employee turnover at a percentage of 46.5% since its creation in 2008 year to December 2020 where the low number of recruited employees compared to the number of employees who exited. This was caused by factors including poor employee compensation, employee overscheduling and employee favouritism. The study discovered that the research objectives were major causes of employee turnover that affected the operational performance of KCB Bank Rwanda at a percentage of 13.8%. Data analysis showed that compensation affected the bank’s operations at a percentage of 73.8% (see table 4.9.), overscheduling at 50.1% (see table 4.7), and favouritism at 56.3% (see table 4.8). The study discovered that the most concern of KCB Bank Rwanda was not the relevance of number of employees who left but the quality of those employee and the targets they had set during the set and submission of the annual balanced scorecard, which affects the operational performance review. The research recommended that the management should review the compensation policy to match the operational performance, reduce favouritism by approaching marginal employees, and reduce overscheduling by re-examining the job descriptions and visiting employee’s office to discover added and non-corresponding duties that attracted the employee turnover in the KCB Bank Rwanda.